Growth And Food Habits Of Pelian Fish Tor Douronensis Caught Using Tuba Root Poison In Krayan Nunukan, North Kalimantan - Dananjaya, IWK Kantun; Hevranklin, Hevranklin; L Rapi, Nuraeni (Fakultas Perikanan dan Ilmu Kelautan Universitas 17 Agustus 1945 Cirebon, 2024)
The use of semah fish with the local name pelian fish in nature is carried out using various methods, one of which is using tuba root plant poison. This tuba root poison is thought to have an impact on the biological condition of pelian fish and aquatic ecology. In connection with this, this research aims to analyze the size distribution, growth type and food habits of pelian fish. The research was conducted from June to August 2023 in West Krayan District, Nunukan Regency, North Kalimantan. The results of the study showed that the length distribution of pelian fish caught using tuba root plant poison was 30.626 ± 7.048 cm, with a weight of 786.531 ± 430.066 g. The growth pattern is negative allometric with eating habits consisting of moss at 44.57%, insects at 33.04%, pieces of fruit at 10.00% and unidentified at 12.39%. Moss and insects are the main food, while fruit is a complementary food. Based on the results obtained, pelian fish in nature can be caught using moss bait. The use of high doses of tuba root can cause damage to the fish's gills, which can cause fish death as a result of not being able to neutralize rotenone.